2018
DOI: 10.1007/s00128-018-2306-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Exposure of Children to Toxic Trace Elements (Hg, Cr, As) in an Urban Area of Yucatan, Mexico: Water, Blood, and Urine Levels

Abstract: Merida is the largest urban center in the Mexican State of Yucatan. Here domestic sewage is deposited in poorly built septic tanks and is not adequately treated. Because of contamination from such waste, water from the top 20 m of the aquifer is unsuitable for human consumption. Given this situation and because children are highly vulnerable to environmental pollution, including exposure to toxic trace elements, this study focused on evaluating the exposure of children to arsenic (As), chromium (Cr), and mercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…However, this study did not find significant correlations of these biomarkers with WAs (Arcega-Cabrera et al, 2017). In a separate study by the same group of researchers on 32 children, BAs above 10 μg/L was reported in 37% of the samples who were exposed to organoarsenic compounds used in the poultry (Arcega-Cabrera et al, 2018).…”
Section: Introductioncontrasting
confidence: 74%
“…However, this study did not find significant correlations of these biomarkers with WAs (Arcega-Cabrera et al, 2017). In a separate study by the same group of researchers on 32 children, BAs above 10 μg/L was reported in 37% of the samples who were exposed to organoarsenic compounds used in the poultry (Arcega-Cabrera et al, 2018).…”
Section: Introductioncontrasting
confidence: 74%
“…Consequently, the V and Cr (with mean HI values of 0.24 and 0.25 for children, Table S2) exposure to the SPM is non-negligible in this study. Considering species-specific toxicity, arsenic (As) mainly afflicts the mucous membrane by directly damaging the capillaries [37,62]; chromium (Cr) can result in asphyxia via reducing oxygen demand of the biochemical process [63]; and vanadium (V) exhibits hepatotoxic, nephrotoxic properties and reproductive system toxicity [64]. Here, we conclude that As is the primary health risk and more attention should also be paid to V and Cr in the Zhujiang River.…”
Section: Resultsmentioning
confidence: 99%
“…Blood serves as a biomarker of recent/short-term arsenic exposure (Arcega-Cabrera et al 2018 ). However, with chronic and continuing exposure, steady-state concentrations are achieved thus blood has the potential to serve as a biomarker of past exposure (Arcega-Cabrera et al 2018 ).…”
Section: Methodsmentioning
confidence: 99%